Initial clinical experience with a misoprostol vaginal insert in comparison with a dinoprostone insert for inducing labor. (May 2016) - Mayer, Richard Bernhard; Oppelt, Peter; Shebl, Omar; Pömer, Joachim; Allerstorfer, Christina; Weiss, Christoph
Abstract: Objective: Only one phase III trial has been published to date on the efficacy and safety of misoprostol vaginal inserts for inducing labor. The aim of this study was to compare misoprostol inserts with dinoprostone inserts. Study design: This retrospective cohort study evaluated the reduction in time to vaginal delivery and delivery within 24 h, in routine clinical work, in 119 labor inductions using a 200-μg misoprostol vaginal insert (Misodel ® ; June–October 2014) in comparison with 124 inductions using a 10-mg dinoprostone insert (Propess ® ; December 2013–April 2014). Results: Vaginal delivery within 24 h occurred in 77.3% ( n  = 92) of the misoprostol cohort and 74.2% ( n  = 92) of the dinoprostone cohort ( P  = 0.654). Time from insert application to vaginal delivery (min) was 761.76 (±409.44, cohort M) versus 805.17 (±473.00, cohort D) ( P  = 0.817). Cesarean delivery was performed in 10.1% ( n  = 12) versus 10.5% ( n  = 13) in the misoprostol and dinoprostone cohorts, respectively ( P  ≥ 0.999). The modified Bishop scores were 2.0 versus 3.0 ( P  = 0.001), mean body mass index (BMI) was 24.72 versus 23.95 ( P  = 0.033), and fetal scalp blood testing was required in 12.6% ( n  = 15) versus 3.2% ( n  = 4; P  = 0.008). No differences were observed with regard to the rates of transfer to the neonatal unit or any type of fetal acidosis. Conclusions: The groups thus had similar results for rates of vaginal delivery within 24 h, cesarean delivery and fetal outcomes. The misoprostol group had lower modified Bishop scores, higher BMIs, and a higher rate of fetal scalp blood testing.